Dinamika Ekonomi Perempuan Perantau dalam Seni Lukis Abstrak - Resa Nurjanah Koswara Putri; Indro Moerdisuroso; Agam Akbar Pahala (Realisasi : Ilmu Pendidikan, Seni Rupa dan Desain, 2026)
This study examines the economic dynamics experienced by migrant women through the perspective of abstract painting as a medium for personal and social reflection. The study uses a qualitative method with an artistic research approach, which departs from the researcher's personal experience as a migrant woman facing increasingly complex economic realities. The rising cost of living, financial constraints, and intertwined academic demands create pressure not only on material aspects, but also on psychological, emotional, and mental conditions. This situation demands adaptation strategies, resilience, and the ability to survive in the face of uncertainty in migrant areas. The dynamics of these experiences are then translated into visual language through an abstract expressionist approach utilizing mixed media techniques. Dynamic line elements, contrasting colors, bubble textures, and layers of material are used as symbols of the tension, struggle, and economic instability experienced by the subjects. The research findings show that abstract painting functions not only as a means of personal expression, but also as a medium for social reflection that records and articulates the experiences of migrant women who are often marginalized. This research contributes to the enrichment of contemporary art discourse, particularly in presenting visual narratives that voice economic issues and women's life experiences in a critical and reflective manner.